Profitability, Capital Structure, And Dividend Policy On Firm Value: The Moderating Role Of Firm Size In The Banking Sector - Velisca, Angela; Pian TA, Suprianus (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study investigates the moderating role of company size in the relationship between profitability, financing structure, and dividend policy on the firm value of banking companies. Methodology: The research employs a quantitative approach using panel data from 23 banking firms listed on IDX Finance over the 2019–2024 period. A fixed effect model with moderated regression analysis is applied to examine interaction effects between company size and key financial variables. Results: The findings indicate that firm size strengthens the positive influence of profitability on firm value, weakens the relationship between financing structure and firm value, and does not moderate the effect of dividend policy on firm value. Novelty: This study introduces firm size as a contextual moderator within banking valuation models in an emerging market setting. Findings: Larger banks experience amplified market sensitivity to profitability, while their capital structure contributes less to valuation compared to smaller banks. Originality: The originality lies in integrating moderated regression analysis with multi-year banking panel data in Indonesia. Conclusions: Firm size plays a critical but asymmetric role in shaping how financial decisions affect firm value in the banking sector. Type of Paper: Empirical Quantitative Research.Type of Paper: Research Article